Plan de negocios para la creación de una empresa dedicada a la exportación de manjar de coco a comunidades latinas en el estado de New Jersey - Jiménez Gudiño, Mayra Alejandra (2017)
The following business plan determinates the viability, feasibility, profitable of starting a company which its main goal is to produce and export coconut jam to Latino communities in the state of New Jersey. Actually, the current market has not the same product as Delicias the coco is offering. Its distinguishing feature is the taste of the product. In order to have a complete market study, both, qualitative research (interviews with experts and consumers) and quantitative (surveys) were developed. The primary data has been obtained by using these tools that allowed us to have a clearer idea of how the target market works. Throughout the project, marketing mix strategies are proposed in order to run its operations. A period of five years has been established to consolidate company operations to be recognized and positioned in the market. It also proposes an organizational structure which company has beginning and presents the production and exporting processes of the product until it reaches its final destination. Finally, a financial plan was executed for a period of five years, which analyzed the real advantages and disadvantages of the companys operation. The analysis also presents financial indicators that enable decision-makers to be interested to invest in the business. Once the market study and the financial analysis were completed, the conclusion is that the project is viable, feasible and profitable. The projects financial indicators determine the viability for investors. The project IRR is 34.44%.